2020
DOI: 10.1111/echo.14605
|View full text |Cite
|
Sign up to set email alerts
|

The effect of colchicine on the echocardiographic constrictive physiology after coronary artery bypass graft surgery

Abstract: Background Constrictive physiology is a transitory condition that could lead to constrictive pericarditis, which is a rare complication after open‐heart surgery. Anti‐inflammatory drugs like colchicine are recommended for prevention of constrictive pericarditis; however, there is no evidence about the effect of colchicine on constrictive pericarditis. Thus, the aim of this study is to evaluate the preventive effect of colchicine on the incidence of echocardiographic constrictive physiology after open‐heart sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…It has been postulated that the modulation of atrial fibrosis by colchicine is mediated by its effects on interleukin-17 and renin-related pathways [ 51 ]. In a trial of patients undergoing coronary artery bypass grafting, perioperative treatment with colchicine was associated with reduction in post-surgical constrictive pericarditis [ 52 ]. In a rat model of hypertension induced by nephrectomy, treatment with colchicine ameliorated both glomerular and interstitial fibrosis in the remaining kidney [ 53 ].…”
Section: Colchicinementioning
confidence: 99%
“…It has been postulated that the modulation of atrial fibrosis by colchicine is mediated by its effects on interleukin-17 and renin-related pathways [ 51 ]. In a trial of patients undergoing coronary artery bypass grafting, perioperative treatment with colchicine was associated with reduction in post-surgical constrictive pericarditis [ 52 ]. In a rat model of hypertension induced by nephrectomy, treatment with colchicine ameliorated both glomerular and interstitial fibrosis in the remaining kidney [ 53 ].…”
Section: Colchicinementioning
confidence: 99%
“…There are 2 reports from the National Inpatient Sample, however these registries refer exclusively to patients from North America, and do not provide extensive information regarding the medical history of the patients and the primary etiology of their disease. 2,22 In our search, we identified only 2 published randomized clinical trials, 23,24 while case reports and small case series comprised a substantial portion of the available literature. Their overrepresentation further mandates the need for a systematic search to identify the true trends of this disease.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis of 6 randomized clinical trials by Salih et al [ 20 ] involving 1257 patients also demonstrated the efficacy of colchicine in reducing the risk of post-operative AF (OR 0.52; 95% CI 0.40–0.68; p < 0.001) [ 20 ]. An interesting randomized, double-blind, placebo-controlled study by Shojaeifard et al [ 21 ] assessed the efficacy of colchicine in the prevention of acute pericarditis (through its influence on constrictive physiology) after cardiac surgery. Patients (n = 160) were randomized to receive colchicine at a dose of 1 mg/day from 48 hours before and 0.5 mg twice/day for 5 days after surgery.…”
Section: Colchicine In the Treatment Of Cardiovascular Diseasesmentioning
confidence: 99%
“…There was no new case of constrictive physiology between weeks 1 and 4 of observation. Thus, the short-term use of colchicine was preventative in reducing constrictive physiology after 1 month of open-heart surgery, but not after a week [ 21 ].…”
Section: Colchicine In the Treatment Of Cardiovascular Diseasesmentioning
confidence: 99%